Wind power and the labor market in the Brazilian Northeast: a spatial propensity score matching approach - Pastorelli Rodrigues, Thiago Antonio (2020)
Debates on the importance of renewable energy sources have arisen in the context of climate change. Wind power is a renewable and clean energy source with minimal environmental impact. Also, the existing literature indicates that the installation of wind farms can be an important channel for local development through job and income generation. In this context, this study aims to analyze the relationship between the presence of wind farms and the labor market outcomes of the municipalities of the Northeast region of Brazil, which contains around 80% of the installed capacity of this technology in the country. The database of this study is built from several public data sources. The methodological approach taken was a combination of propensity score matching and the estimation of the average treatment effect. However, we consider the existence of spatial dependence of the municipalities in the estimation of the propensity score. The results suggest that the presence of wind power plants is positively related to increases in the total wage of the municipalities, mostly in sectors such as construction, transportation, and logistics. In addition, the presence of these plants allows the shifting of resources to the agricultural sector.